Turkish-Balkan policy after the cold war - Kelkitli, Fatma Aslı. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2005., 2005)
This thesis examines the Turkish-Balkan policy since the establishment of the Republic until now. Special emphasis is given to the period after the end of the Cold War as Turkish foreign policy gained several new aspects and experienced significant changes during this era. With the dissolution of the Soviet Union and collapse of the communist regimes in the Balkans, the Iron Curtain which divided Turkey and Balkan states disappeared and these developments brought out a renewed Turkish interest and involvement in the region. However this early optimism gave way to stability and security concerns with the bloody disintegration of Yugoslavia and the emergence of new conflicts and wars in the Balkans. Turkey had to bring forth new approaches and policies in order to face the difficulties in this volatile geo-political environment. In this context, diplomatic initiatives towards the solution of the Bosnian and Kosovo crises and Turkish attempts to improve bilateral relations with the Balkan states were explored in details in this thesis. After the end of the Kosovo War the EU and the US accelerated their efforts to integrate the Balkans into the Euro-Atlantic institutions. This thesis also attempts to find out the role of Turkey in this new economic, political and security structures in the Balkans.